De Boucherville v. State of Mauritius. (2014) - Unknown
Abstract : 466 Human rights — Right not to be subjected to inhuman or degrading punishment — Constitutional guarantee — Whether breached in respect of appellant — Appellant receiving mandatory death sentence — Appellant awaiting execution on death row — Whether constituting inhuman and degrading punishment — Whether breaching Section 7 of Constitution Human rights — Right to a fair hearing — Constitutional guarantee — Whether breached in respect of appellant — Appellant sentenced to death — Abolition of death penalty — Appellant's death sentence deemed to be sentence of penal servitude for life — Comparison of mandatory death sentence and mandatory life sentence — Whether mandatory life sentence disproportionate and arbitrary — Whether any safeguards existing — Whether possibility of intermediate release — Whether mandatory life sentence would have violated Articles 3 and 5 of European Convention on Human Rights, 1950 — Effect and constitutionality of mandatory life sentence — Whether mandatory life sentence contrary to Section 10 of Constitution — The law of Mauritius